How many trials are needed to assess ankle joint proprioception in children with chronic ankle instability? - Jaruta Kunritt (2022)
The assessment of ankle joint repositioning is commonly used to detect joint impairment in people with chronic ankle instability (CAI). To decrease measurement fluctuation errors, it has been suggested that an average of 10 measurements be utilized. However, learning and tiredness difficulties, particularly in children, might make this difficult. Therefore, this study aimed to compare the repeatability of 3 and 10 measures of ankle joint repositioning using an isokinetic dynamometer (Biodex) in children with CAI. Ten children with CAI with an average age of 11.21 years were recruited in the study. The ankle inversion and eversion angles for 3 and 10 trials using active and passive reproduction protocols were recorded using Biodex Multi-Joint System 4™. The error of reproduction angle was presented by the mean, correlation, and percentage changes for both active and passive reposition angles. The means of the error for ankle joint reproduction angles revealed no significant differences between 3 and 10 trials for both active and passive protocols (p > 0.05). The ICC(3,k) revealed high correlations between 3 and 10 trials of assessments (ICC(3,k) = 0.82-0.91). The percentage changes of means and standard deviations showed learning effect of ankle joint proprioception measurement after the 4th and the 5th trials for inversion and eversion, respectively. Therefore, to prevent learning and fatigue effects, a 3-trial protocol would be more appropriate than a 10-trial protocol. However, a 4-trial protocol and a 5-trial protocol were suggested for inversion and eversion, respectively. The suggested protocols are recommended to use for further reliability studies of the ankle joint proprioception in children with CAI.